Attitudes of Prospective EFL Teachers toward Teaching Profession - Thouqan Saleem Masadeh (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
This study aimed to investigate Saudi Pre-service EFL teachers' attitudes toward the teaching profession. Viewpoints of Forty-two student teachers enrolled in the "Practicum" course offered by Najran University were investigated. Results of gathered data analysis showed that the attitudes of participating subjects were positive due to many factors. Among these factors is their belief that the EFL teaching profession is one of the most popular professions in Saudi Arabia. They seemed sure that EFL teaching as a noble, prestigious, and interesting profession would make them proud of themselves as teachers of English. In addition, their hope to be able to try applying their gained pedagogical and academic knowledge from teacher training courses at university significantly affected their positive attitudes. Therefore, the majority of them believed that with some kind of professional commitment, they would be successful EFL teachers.